Community Radio: Preferences, Opinion and Listening Behaviour of Farmers (Indian Journal of Extension Education, 2015)
Community radio is an innovative tool for community empowerment catering information needs of the farming community in rural and remote areas in a radius of about 15 kms. The study was conducted in purposively selected five community radio stations during 2012 to 2014. Five community radio stations i.e. CCSHAU, Hissar (Haryana), Vallabh Krishak Radio, Saharanpur (Uttar Pradesh), Community Radio, Mewat (Haryana), Pravara Community Radio, Babhaleshwar (Maharashtra) and Sharda Community Radio, Baramati (Maharashtra) were selected for the study. Two villages each were selected randomly from each CRS jurisdiction to see the farmers’ responses about the community radio station. Fifteen (15) respondents’ were selected randomly from each of the sampled ten villages. Thus, a total of 150 respondents from five CRS constituted the sample for the study. The study revealed that a majority (65 %) listeners preferred agriculture success stories followed by live interactive programme (60 %), experts talk on agriculture and GK test in agriculture (57.50%). Also a majority (52.67%) of the respondents were daily listeners of the community radio programmes followed by weekly (30%) and fortnightly (17.33%). Major strengths of CRS identified were interesting due to local dialect (2.6 MS) followed by quick source of information (2.5 MS), and community participation (2.3 MS). The major weaknesses of CRS identified were problems of sustainability (2.5 MS), followed by low (15 kms) coverage (2.3 MS), low power (50 W) transmitter (2.00 MS) and no operating cost (1.8 MS). Also listening pattern of the respondents revealed that 57.33 per cent listeners were listening CR programme and simultaneously doing some work like cooking, feeding animals, milking etc. followed by about 23 per cent respondents were listening and taking notes.